HUMAN, CHANGE AND URBANIZATION: RURAL COMMUNITIES DYNAMICS AS SOCIO-CULTURAL AND ECONOMIC RESOURCES - Sriyanto, Sriyanto (Universitas Muhammadiyah Purwokerto, 2014)
Interaction between rural and urban generates a contradiction in economic, cultural,social, political and even symbols oflifestyle of rural communitieswhich perceive themas a cynical society.The development of information and technology has made animpact onshifting the rural community to modernity and transform the societythroughthe elements of social resources. The increasing complexity of life has affected rural andurban interaction, human need to adjust to the advanced demands of life throughmeans of education, socio-cultural, economics and technology. These aspectsintensifythe interaction between the rural and the urban through the gravity of eachregion. Gravity model is used to enhance the role of each region to improve the socioculturalandeconomic resources.Keywords:gravity,interaction, rural, urban.